Myokines may target accelerated cognitive aging in people with spinal cord injury: A systematic and topical review. (March 2023) - Vints, Wouter A.J.; Levin, Oron; Masiulis, Nerijus; Verbunt, Jeanine; van Laake-Geelen, Charlotte C.M.
Abstract: Persons with spinal cord injury (SCI) can suffer accelerated cognitive aging, even when correcting for mood and concomitant traumatic brain injury. Studies in healthy older adults have shown that myokines (i.e. factors released from muscle tissue during exercise) may improve brain health and cognitive function. Myokines may target chronic neuroinflammation, which is considered part of the mechanism of cognitive decline both in healthy older adults and SCI. An empty systematic review, registered in PROSPERO (CRD42022335873), was conducted as proof of the lack of current research on this topic in people with SCI. Pubmed, Embase, Cochrane and Web of Science were searched, resulting in 387 articles. None were considered eligible for full text screening. Hence, the effect of myokines on cognitive function following SCI warrants further investigation. An in-depth narrative review on the mechanism of SCI-related cognitive aging and the myokine-cognition link was added to substantiate our hypothetical framework. Readers are fully updated on the potential role of exercise as a treatment strategy against cognitive aging in persons with SCI. Graphical Abstract: ga1 Highlights: Persons with SCI suffer accelerated cognitive aging, even in the absence of TBI. Neuroinflammation may mediate the accelerated cognitive aging following SCI. Myokines are anti-inflammatory & neurotrophic factors released with muscle training. Muscle training may target neuroinflammation and improve cognition following SCI. So far, no studies have investigated the myokine-cognition link in people with SCI.